Postoperative Serum Creatinine Serves as a Prognostic Predictor of Cardiac Surgery Patients - Hou, Jian; Shang, Liqun; Huang, Suiqing; Ao, Yuanhan; Yao, Jianping; Wu, Zhongkai (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background: To investigate the significance of postoperative serum creatinine in predicting the prognosis of cardiac surgery patients. Methods: Clinical data were extracted from the Medical Information Mart for Intensive Care III (MIMIC-III) database. Adult (≥18 years) cardiac surgery patients in the database were enrolled. The association of serum creatinine with ICU stay and hospital mortality was analyzed with Spearman correlation and Chi-square tests. Multivariable logistic regression was used to identify creatinine as an independent prognostic factor for hospital mortality. Results: In total, 6001 patients who met the selection criteria were enrolled in our study, among whom, 108 patients (1.8%) died in the hospital. Nonsurvivors had much higher serum creatinine levels (initial: 0.8 vs. 1.2, P<0.001; max: 1.1 vs. 2.8, P<0.001; min: 0.8 vs.1.1, P<0.001). Positive correlations were observed between serum creatinine (P<0.001) and ICU stay. For all Models, creatinine initial (Model 1: OR=1.411, 95%CI =1.172-1.700, P<0.001; Model 2: OR=1.326, 95%CI=1.101-1.596, P<0.001; Model 3: OR=1.361, 95%CI=1.198-1.547, P <0.001), creatinine max (Model 1: OR=1.901, 95%CI =1.675-2.157, P<0.001; Model 2: OR=1.768, 95%CI=1.550-2.016, P<0.001; Model 3: OR=1.644, 95%CI=1.473-1.836, P <0.001), and creatinine min (Model 1: OR=1.595, 95%CI =1.246-2.043, P<0.001; Model 2: OR=1.399, 95%CI=1.069-1.831, P<0.001; Model 3: OR=1.465, 95%CI=1.174-1.828, P <0.001) were all positively associated with hospital mortality. The diagnostic performance of creatinine was moderately good (area under the curve (AUC) for creatinine initial =0.7583; AUC for creatinine max =0.8413; AUC for creatinine min =0.7063). Conclusions: This study demonstrated the potential to use postcardiac surgery serum creatinine as outcome indicator.